Simulation of Deformation and Fracture Characteristics of a 45 Steel Taylor Impact Specimen - CHEN, Gang; HUANG, Xicheng (Engineering Transactions, 2016)
The Taylor impact test was originally developed as a method for estimating the dynamic strength of ductile materials at high strain rates. More recently, the Taylor test has been used to verify material constitutive models by comparing numerical predictions with experimental data, since it provides a wide range of plastic strains and strain rates in various stress states. When the impact velocity is sufficiently high, a specimen will generate cracks in the Taylor test. Only few studies investigated so far the fracture phenomena and mechanisms in the Taylor test. In this paper, based on investigation of material dynamic behaviour, the deformation and fracture characteristics of a 45 steel specimen under Taylor impact test were simulated using axial symmetry and three-dimensional model was developed with LS-DYNA software. The final length and diameter of the specimen, obtained in simulations, were consistent with the experimental observations. Different dynamic fractures that occurred in the Taylor test were obtained in three-dimensional numerical simulations as well. The mechanisms of different failure modes were investigated using the history of stress state triaxiality of the specimen.